PENGEMBANGAN MODUL MEMBACA DAN MENULIS BERBASIS UJI DIAGNOSTIK UNTUK MENINGKATKAN PEMAHAMAN SISWA SMP TERHADAP MATERI POKOK BAHASA INDONESIA - Suhartono Suhartono; J. Parmin; Yermia Nugroho Agung Wibowo (Center of Language and Cultural Studies, 2015)
The objective of this study is to devise a Diagnostic-Test-Based of Reading and Writing Module of Bahasa Indonesia for SMP students. The study fcuses on the instructional design of the core materials of Bahasa Indonesia in the School-Based Curriculum. The study uses Research and Development design implementing three circles of activity: planning, designing and development. Research subjects included 27 ninth gragers of SMPN 28 Surabaya. The study reveals that in the planning stage, core materials of reading and writing were selected by the schools and be listed as Table of Specification before National Leaving Exam. Analysis of diagnostic test indicated that core materials of reading and writing for Bahasa Indonesia deviated problems students faced so that students received no benefits. The development of the module empirically proved that Diagnostic Test-Based Reading and Writing module increased students accomplishment up to 23.03%.